The Implementation of Ecocriticism Approach for Healthy Earth and strengthen the English skill of Literary Appreciation Class at Islamic University of Majaphit – Mojokerto AHMAD IKLIL SAIFULLOH, S.S., M.PD - saifulloh, ahmad iklil (Universitas Nurul Jadid, 2019)
Due to the research by Greenpeace and Air Visual IQ published on March 5 2019, monitored air quality in hundreds of cities across the globe, Jakarta was ranked first. In accordance with educational character based on Indonesian curriculum about 18 standard characters interpreted, and one of them was environmental care. The problem was the way a teacher to blend those characters into a good educational system in the class. In fact there were no definite process to transfer that character to the student in term of plan, proses, content, and evaluation. It proofed that there were many difficulties by the teacher to conduct evaluation to the student about their character because the teacher only focuses on a cognitive area. So that’s why this research try to transform the area of ecology and education to solve those conditions. Due to the condition, the researcher tends to strengthen the educational method on the field of Ecology with Literary Criticism as the media with the title The Implementation of Ecocriticism Approach for Healthy Earth and strengthen the English skill of Literary Appreciation Class at Islamic University of Majaphit – Mojokerto.